Tolerância social no uso ferramentas por macacos-prego em área de manguezal - CONCEIÇÃO , Daiana Paulino da (2019)
The capuchin monkeys of Sapajus sp. gender are primates that developed the tool use ability to assist in the food process, a common behavior in many groups, but absent in others, which may characterize a diffusion through social learning opportunity, facilitated by possible tolerance behavior in the social relationship. In this context, this study had as objective check for any relationship between social tolerance and tool use and so investigate the influence of social tolerance in the observation of conspecific in interaction networks during provisioned feeding of capuchin monkeys who live in mangroves. The study was performed in a group of capuchin monkeys that inhabit the mangroves of the North coast of Brazil. To test the hypotheses and identify the tolerance degree between individuals were conducted 69 experimental sessions and collected behavioral data through filming using feeding platforms provided with crabs (Ucides cordatus) collected near the study area. For each feeding episode were recorded the animals involved in the action and the conspecific with whom they had contacts. To data analysis were constructed interaction networks and all interactions were compiled in interaction, proximity and observation frequency matrices which were viewed and analyzed in Gephi software. The results showed that there is a correlation between the variables Observation Time of the conspecific and the Time Eating Together with the proximity between the individuals during the feeding episodes. The network analysis showed a strong interaction between the focal and conspecifics, and the centrality analysis highlighted four central individuals in the networks, but which maintains a strong connection with visiting individuals. Therefore, our results suggest that in this group of capuchin monkeys, those individuals who find themselves in a more central position have a high index of social tolerance where all individuals, proficient or not, can observe their conspecific in feeding activities, even when there is no significant proximity.